Research on the Performance of AlCrSiWN Tool Coatings for Hardened Steel Cutting - Guo, Feng (International Journal of Mechanical and Electrical Engineering, 2025)
This study compares the cutting performance of uncoated, as-deposited, and annealed AlCrSiWN-coated tools during dry machining of hardened steel. The uncoated tool failed within 8 minutes, exhibiting rapid wear (VBmax=300 μm) and thermal shock (5.2 °C/min). The as-deposited coating maintained steady wear (89.8-247.5 μm) for up to 60 minutes, but experienced abrupt wear acceleration to 569.7 μm at 90 minutes due to brittleness. The annealed coating extended wear life to 110 minutes with a final VBmax of 647.5 μm, demonstrating uniform wear progression and a 22% reduction in heating rate at 20 minutes. Temperature spikes (4.4-13.3°C/min) during severe wear correlated with expansion of the triangular wear band. Annealing effectively mitigated brittle fracture by facilitating plastic deformation, confirming its significant enhancement of coating durability under high-temperature cutting conditions.